Development and reactivity of the immune system of Japanese quail lines divergently selected for the shape of the growth curve. Issue 6 (2nd November 2019) - Kankova, Z.; Drozdova, A.; Klobetzova, Z.; Lichovnikova, M.; Zeman, M.
ABSTRACT: 1. Selection strategies for broilers must balance rapid growth with the welfare and health of animals, strategies must deal with the trade-off with other vital functions. 2. Divergent selection of Japanese quail for high (HG) and low (LG) relative body weight gain between 11 and 28 days of age has been conducted to accelerate linear phase growth without influencing the final adult body weight. Higher body growth rate is often connected with a weakened immune system. Therefore, the present study explored the immunological characterisation of quail from HG and LG lines, which differ substantially in their growth rate. 3. The trial evaluated the maternal investment to immunologically active substances, cell-mediated immunity stimulated by phytohaemagglutinin (PHA) injection and the acute phase of the immune response to lipopolysaccharide (LPS) administration in three different phases of early postnatal growth. 4. Except for higher lysozyme activity in the LG group when compared to the HG line, the maternal investment did not differ between the two lines. Plasma antibody concentrations responded quickly to any change in growth rate in both lines. Overall, it seems that initial rapid growth of the LG line had long-lasting effects on immune responsiveness, even after the growth rate of the HG line escalated during the linear phase of growth. 5. The study indicated that changes in the growth rate caused by the selection for growth in meat-type Japanese quail can influence the acute phase of the immune response and development of the immune system.